Values of Islamic Education in Ustadzah Oki Setiana Dewi Youtube Lecture - Abid Nurhuda; Nur Aini Setyaningtyas (LPPM Politeknik Raflesia, 2022)
Islamic education has experienced ups and downs since ancient times along with the emergence of various kinds of challenges of the times. especially in today's era where everything is digital and technological, so most only want increased interaction, technology orientation and acceleration. Even though the true purpose of Islamic education is to give birth to complete human beings, namely faith and noble character, so that one of the steps to overcome this is by utilizing technology in spreading various positive impacts through social media. This includes spreading Islamic education through the YouTube channel, and one of the lecturers who uses this technology is Ustadzah Oki Setiana Dewi. The purpose of this study is to describe the values of Islamic education in his YouTube lecture entitled